MAKING DIAGNOSTIC WAX UP OF MAXILLARY ANTERIOR TEETH IN CROSS BITE CASES - Sri Redjeki Indiani; Sianiwati Goenharto; Anisa Nur Halimah; Widiya Ulfa; Narta Nikita Sari; Winda Kusumawardani; Dinda Nur Agustin (Journal of Vocational Health Studies, 2025)
Background: An anterior crossbite is a type of malocclusion in which one or more maxillary anterior teeth are positioned lingually to the mandibular anterior teeth, compromising aesthetics and reducing patient confidence. A thorough understanding of the patient's chief complaint is essential for developing an effective treatment plan. A diagnostic wax-up is recommended to improve predictability and facilitate the modification of maxillary and mandibular relationship ultimately enhancing aesthetic outcome. Purpose: To describe the procedure for creating a diagnostic wax-up of the maxillary anterior teeth in an anterior crossbite case for aesthetic purposes. Case analysis: Maxillary and mandibular working models were received, showing an anterior reverse bite malocclusion, with an overjet of -3 mm and an overbite of 2 mm. The dentist requested a diagnostic wax-up of the maxillary anterior teeth to achieve optimal aesthetic results. Result: The master model was received, marked, occluded, and mounted on an articulator. Wax was then applied and shaped to refine the anatomy of tooth 21, with the point and line angles adjusted toward the center to create a smaller appearance while carefully considering the height and convexity. Wax restorations were made covering 6 anterior teeth from maxillary left canine to maxillary right canines with the occlusal relationships adjusted to approximate a normal appearance. Conclusion: The diagnostic wax-up procedure involves preparing the working models, establishing the median line, mounting the models on an articulator, and sequentially waxing teeth numbers 11 and 21 first, followed by teeth 12 and 22, and finally teeth 13 and 23. The overjet is increased to achieve a more normal maxillomandibular occlusion, followed by careful evaluation.